2019
DOI: 10.4103/aam.aam_15_18
|View full text |Cite
|
Sign up to set email alerts
|

Platform switching technique and crestal bone loss around the dental implants: A systematic review

Abstract: Background:The overall success of dental implants depends on the crestal bone support around the implants. During the initial years of dental implant placement, the bone loss around the implants determines the success rate of treatment. Platform switching (PLS) concept preserves the crestal bone loss, and this approach should be applied clinically for the overall success of dental implants.Purpose:The purpose of this study is to discuss the literature dealing with the concept of PLS concept and preservation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
1
21
0
3
Order By: Relevance
“…Additionally, the present results are consistent with the preliminary 1year results with the same implant system published by Moergel et al [17]. The integrated platform switching of the implants might additionally contribute to the stabilization of the bone as reported in several studies [21,22,27,36].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, the present results are consistent with the preliminary 1year results with the same implant system published by Moergel et al [17]. The integrated platform switching of the implants might additionally contribute to the stabilization of the bone as reported in several studies [21,22,27,36].…”
Section: Discussionsupporting
confidence: 93%
“…Features of the chosen implant system for a study may also influence the outcome of the treatment: The degree of the manufacturer's tolerances of implants with a conical implant-abutment connection heightens the risk of a mispositioning of the abutment, which cannot be corrected by repeated torqueing. Platform switching (PS) implants tend to have a protective effect on hard implant tissue outcomes, while implants with sandblasted, acidetched surfaces allow for a shortened unloaded healing period [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Thread exposure can be influenced by the time after implant insertion, and bone loss up to 2 mm in the first year of implant placement is expected and acceptable. 17 As this was a retrospective cross-sectional study based only on image evaluations, this clinical information was not available, making it impossible to consider whether thread exposure occurred due to bone loss or insufficient insertion. In contrast, when evaluating implant thread exposure on immediate postoperative CBCT scans, Clark et al 2 found only 4 cases (out of 160 implants with some error), classifying them as implants with insufficient insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Implants placed in patients with osteoporosis do not lead to a higher complication rate than those placed in patients without osteoporosis. 9 Data from literature confirms that not only surgical insertion of dental implants is a potential risk factor for the development of osteonecrosis but also the presence of the implant into the bone can be associated with this disease. Patients should be informed about the increased risk for the medication-related osteonecrosis of the jaw.…”
Section: Discussionmentioning
confidence: 93%